Termometer Non Contact Menggunakan Sensor Suhu Infrared MLX90614 Sebagai Pengukur Suhu Tubuh Berbasis SMS GateWay: Non Contact Thermometer Using Infrared Temperature Sensor MLX90614 As Body Temperature Measuring Body Based On SMS Gateway - Tanjung, Ibnu Habibi (Institut Riset dan Publikasi Indonesia, 2022)
In 2020, the COVID-19 pandemic is a threat to countries around the world, as well as Indonesia. The spread of the Corona virus in Indonesia is still not well contained. There are many ways to prevent the spread of the corona virus, one of which is by checking body temperature. The normal body temperature range is between 36.5-37.5 ºC. Therefore, a technology is needed to assist in suppressing the spread of the Corona virus and provide alternative options as a medium for non-contact body temperature measurement and the need to convey information if there is a body temperature that exceeds the normal limit to the authorities so that can be followed up. Therefore, an innovative Non-Contact Thermometer was created using the MLX90614 Infrared Temperature Sensor as an SMS Gate Way Based Body Temperature Measurement with input in the form of an HCSR04 Ultrasonic sensor and output in the form of an LCD display, buzzer, and LED as an alarm as well as a short message (SMS) warning to the operator. when body temperature > 37.5 ºC. This prototype has the additional feature of measuring room temperature. This prototype has been tested in sensor readings with a distance of 5 cm with several participants and the test results are compared with the results of the thermogun. The test results show that the prototype in measuring body temperature has an average difference of 0.10 ºC and the average value of the difference in measuring room temperature is 0.25 ºC.